Mów Mi Marianna - Bielawska, Karolina (Poland : Film Republic, 2016)
Marianna is an attractive 40-year-old woman who sued her parents in order to obtain the sex change she has always desired. Alienated by her mother but neglecting her best friends, she sought refuge in a theatre group where she came to make sense of her situation by rehearsing a play based on her history. Marianna sparks an unlikely romance with an older gentleman who offers her a ray of hope, she remains confronted by the idea of losing what she holds dearest to her, her family, as she faces the chilling reminder of the sacrifices one takes to be themselves. 'Call Me Marianna', the opera prima by Karolina Bielawska, is an homage to the freedom of identity and the unpredictable alternatives life can offer.
Verzio Film Festival Submission
Keywords: Documentary films